2018
DOI: 10.3766/jaaa.17114
|View full text |Cite
|
Sign up to set email alerts
|

Face and Content Validity of a Probe Tube Placement Training Simulator

Abstract: Background: Probe tube placement is an important skill audiologists must learn to make real-ear measurements in an audiology clinic. With current evidence-based guidelines recommending insertion of the probe tube within 5 mm of the tympanic membrane (TM) for proper acoustical measurements, students must be well trained to ensure they are capable to perform this placement in clinical practice. This is not always the case as it has been found that real-ear measurements are not performed in a clinic as often as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…I n medical simulator research, a typical validation sequence consists of a qualitative study aiming to receive early-stage feedback (face and content validity), backed with quantitative studies to prove its utility within educational settings (construct validity, discriminant validity, and skill transference validity). Our previous study (Koch et al, 2018) confirmed the simulator's training ability and provided feedback to guide the product development discussed previously. The present study accomplished a second-level evaluation of the developed audiology training simulator.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…I n medical simulator research, a typical validation sequence consists of a qualitative study aiming to receive early-stage feedback (face and content validity), backed with quantitative studies to prove its utility within educational settings (construct validity, discriminant validity, and skill transference validity). Our previous study (Koch et al, 2018) confirmed the simulator's training ability and provided feedback to guide the product development discussed previously. The present study accomplished a second-level evaluation of the developed audiology training simulator.…”
Section: Discussionsupporting
confidence: 73%
“…Briefly, the simulator consisted of an artificial adultsized head with a pliable, realistic ear and a camera mounted within the head to measure the probe-tube insertion depth using an associated custom-developed software package. The original simulator has been previously described by Koch et al (2018) and used a Styrofoam head that lacked realism as the first-generation prototype. Several improvements were made based on suggestions from the participants in the first validation study.…”
Section: Simulatormentioning
confidence: 99%
See 1 more Smart Citation
“…aheadsimulations.com/carl-for-training). They are used to train hearing aid manipulation, the removal of cerumen, real-ear unaided response measurements, and high-gain hearing aid fitting [21,22]. Some computerized simulations allow training for specific tasks such as otoscopy, pure-tone air and bone conduction audiometry with online virtual patients [23].…”
Section: Plos Onementioning
confidence: 99%
“…Using the functional system put forth herein, future work will continue along two main paths in tandem: 1) validity and skill transference studies and 2) the development of standalone mass-spring framework that will be released as an asset on the Unity asset store for public use. Similar to work conducted previously in the lab for an audiological probe tube simulator (Koch et al, 2018), face and content validity will be assessed with feedback from additional otolaryngologists and medical students. After incorporating the feedback into the simulator, skills transference can proceed and the efficacy of the simulator can be quantitatively assessed.…”
Section: Resultsmentioning
confidence: 99%